Analysis of the Saw System with the PANI + Nafion Sensing Structure for Detection of Low Concentration Carbon Monoxide - HEJCZYK, Tomasz; PUSTELNY, Tadeusz (Archives of Acoustics, 2020)
The paper presents a measuring system based on two resonators with a SAWacoustic surface wave. One of the resonators contains a sensor structure consisting of a Nafion layer with a PANI polyaniline nanolayer deposited on it. The sensor structure was tested for carbon monoxide, with a very low concentration (5, 10, 15, 20 ppm) in the atmosphere of synthetic air. The structure sensitivity was tested for two different PANI thicknesses: (100 and 180 nm). The tests were carried out for two different temperatures: 308 K and 315 K. The investigations shows that the measuring system used with the acoustic surface wave together with the proposed sensing layers is sensitive to the presence of low concentration carbon monoxide molecules in the atmosphere of synthetic air.